Nonsuperoxide lucigenin-enhanced chemiluminescence from phospholipids and human saphenous veins - Capomacchia, Anthony C. (1995)
The use of lucigenin-enhanced chemiluminescence (CL) for the detection of superoxide (O2·−) has grown in popularity due to an increased demand for a simple and specific system capable of measuring superoxide. In this study we report a lucigenin-CL signal emanating from human saphenous veins (SV) that was not inhibited by superoxide dismutase (SOD) and lasted for more than 24 h. A larger CL-signal with similar properties was produced by saphenous veins that had been dehydrated. A similar, non-SOD-inhibitable lucigenin-CL was also produced with a variety of phospholipids and phosphatidic acid. The chemical moiety responsible for the phospholipid CL is oxygen dependent but remains unidentified because a variety of lipids and phosphate containing species failed to produce such a signal. These results suggest that the use of lucigenin as a specific CL enhancer for O2·− must be clearly discriminated with a specific O2·− inhibitor when used in biological systems.